APLIKASI METODE PSEUDO 3D SEISMIK DI CEKUNGAN JAWA BARAT UTARA MENGGUNAKAN K.R. BARUNA JAYA II - Trevi Jayanti Puspasari; Sumirah Sumirah (Laboratory for Marine Survey Technology, 2020)
[Aplication of Seismic Pseudo 3D in Nort West Java Basin Using K.R. Baruna Jaya II] The demand to follow the growth of needs in the oil and gas industry is a motivation in the developing of techniques for assessment and applying 2D multichannel seismic acquisition. The development of exploration needs for the oil and gas industry is not matched by budget for an upgrade Government’s seismic equipment including equipment installed in K.R. Baruna Jaya II. Applied Pseudo 3D method in survey and seismic data processing can be an effective and efficient solution. The pseudo 3D method is a data acquisition and processing technique with an emphasis on the acquisition design and 2D seismic data processing innovation to produce a 3D seismic volume. This study aims to apply the pseudo 3D seismic method in the North West Java Basin using the K.R. Baruna Jaya II which was held in Desember 2009. As a Result, advanced seismic processing was carried out to output a seismic volume (3D) profile. This profile can be used as a reference in making decisions and planning the next survey. Keywords: Pseudo 3D Seismic, Seismic 2D multichannel, K.R. Baruna Jaya II, Nort West Java Basin.